گرنگی گرافیک دیزاین لە ناو هونەری شێوەکاری هاوچەرخ لە هەرێمی کوردستانی عێراق دا (توێژینەوەی هەڵێنجراو) - سەعید, ڕێبوار; عوێز, نەرمین مصطفى (Sulaimani Journal for Humanities, 2023)
The problem of this research is to answer the following question: whether graphic design in the process of producing artwork and contemporary art at a certain level is part of contemporary art in the Iraqi Kurdistan Region? The aim of this study is to show the importance of graphic design within the plastic arts at the present, especially in the Iraqi Kurdistan Region (Suleimani) as an example. The importance of this research is that it works on graphic design artworks in the field of contemporary plastic arts, which has its importance for the art centers and art students in universities and colleges, especially those students who study graphic design. Analytical descriptive methods were used to conduct the study. The research community consists of a number of graphic designs works and projects, that have a recent history and are available in detail after research and collection of works for this purpose, in Suleimani from 2012 to 2022. The study sample was the same as the study community, through non-random sampling. The importance of this research and efforts are focused on the significance of graphic design and different types of graphic printings, on the surface of different stages of creating a contemporary work of art that eliminates all boundaries between artistic genres. That goes in the direction of achieving contemporary work. As a result of the research, the researcher has reached several points, the most important of which is that graphic design in the process of producing contemporary artwork is part of contemporary art in the Iraqi Kurdistan Region, Sulaimani for example, At the same time, graphic design relies on new media as a technical medium for the production of artworks, Then the recommendations and suggestions are presented, and the paper is concluded with a list of sources used.